Analyzing the Effects of Low-Dose Isotretinoin on Acne Vulgaris Against the Standard Treatment Protocol - Areeba Jabbar, Naimat Ullah, Annum Shahzadi, Afshan Sagheer, Hafiz Muhammad Imran Aziz, Amna Asghar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study’s objective was to evaluate the effectiveness and safety of low-dose isotretinoin vs the standard-dose regimen for the treatment of acne vulgaris. Study Design: Randomized controlled trial Place and Duration: This study was conducted at Department of Dermatology, Bannu Medical College and Federal Government Polyclinic Hospital Islamabad in the period from March, 2022 to August, 2022. Methods: Randomization was used to split the total of 190 patients with acne vulgaris who participated in the study into two groups of 95 sample size each. Patients of both sexes were affected with acne vulgaris. Isotretinoin was administered orally to patients in group I at a dose of 20 milligrammes per day for 12 weeks, whereas patients in group II received conventional dosing regimen 80 milligrammes per day. After a total of 12 weeks of therapy, both groups had a final assessment of their effectiveness. SPSS 23.0 was used to analyze all data. Results: In all 190 cases, majority of the cases 110 (57.9%) were females and 80 (42.1%) were male patients. Mena age of the patients in group I was 24.16±10.52 years and in group II mean age was 25.8±9.87 years. We found that efficacy of conventional dosing regimen was higher in 73 (76.8%) as compared to low doze isotretinoin in 50 (52.6%) with p value <0.005. Post-treatment frequency of complication were higher in group II 46 (48.4%) as compared to group I 28 (29.5%). Dry eyes and headache were the common complications in all cases. Conclusion: As a result of this research, we came to the conclusion that the typical dosing regimen for the treatment of acne vulgaris is more effective but poses a greater risk of side effects than the low dose of isotretinoin. Keywords: Efficacy, Safety, Acne vulgaris, low dose isotretinoin